An evolutionary perspective on gradual formation of superego in the primal horde - Pulcu, Erdem (Frontiers in Psychology, 2014)
Freud proposed that the processes which occurred in the primal horde are essential for understanding superego formation and therefore, the successful dissolution of the Oedipus complex. However, Freud theorized superego formation in the primal horde as if it is an instant, all-or-none achievement. The present paper proposes an alternative model aiming to explain gradual development of superego in the primitive man. The proposed model is built on knowledge from evolutionary and neural sciences as well as anthropology, and it particularly focuses on the evolutionary significance of the acquisition of fire by hominids in the Pleistocene period in the light of archaeological findings. Acquisition of fire is discussed as a form of sublimation which might have helped Prehistoric man to maximise the utility of limited evolutionary biological resources, potentially contributing to the rate and extent of bodily evolution. The limitations of both Freud's original conceptualisation and the present model are discussed accordingly in an interdisciplinary framework.